2012
DOI: 10.1111/j.1464-0597.2012.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Expertise Affirmation and Shared Expertise Perceptions in Work Teams: Their Implications for Coordinated Action and Team Performance

Abstract: In this paper we argue that reciprocal expertise affirmation-i.e. the mutual recognition by team members that they respect, value, and affirm each other's expertise-is positively related to team performance, but only in teams with high levels of shared expertise perceptions. Moreover, we propose that the joint effects of teams' reciprocal expertise affirmation and sharedness of expertise perceptions on team performance will be mediated by coordinated action. Data from 226 members of 39 student teams, working o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 61 publications
4
24
0
Order By: Relevance
“…From a theoretical standpoint, human factors and detrimental team processes in HRTs (including conflict, asymmetry perceptions and stress and coping appraisals) have largely been overlooked in the literature, despite that these variables contribute to the success or failure of emergency responses more than other variables combined (Grutterink et al, 2012;Mas et al, 2013;Ramarajan et al, 2004Ramarajan et al, , 2011Waller and Jehn, 2000;Weldon et al, 1991). In this article, we seek to remedy this issue by proposing a novel conceptual framework.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…From a theoretical standpoint, human factors and detrimental team processes in HRTs (including conflict, asymmetry perceptions and stress and coping appraisals) have largely been overlooked in the literature, despite that these variables contribute to the success or failure of emergency responses more than other variables combined (Grutterink et al, 2012;Mas et al, 2013;Ramarajan et al, 2004Ramarajan et al, , 2011Waller and Jehn, 2000;Weldon et al, 1991). In this article, we seek to remedy this issue by proposing a novel conceptual framework.…”
Section: Resultsmentioning
confidence: 95%
“…social systems, conflict, characteristics of HRTs), by contrast, have been largely understudied. Yet research examining workgroups and teams in organizations shows that human factors explain more of the variance in team success or failure than other factors combined (Grutterink et al, 2012;Mas et al, 2013;Ramarajan et al, 2004Ramarajan et al, , 2011Waller and Jehn, 2000;Weldon et al, 1991). Therefore, we propose that it is imperative to pay more attention to human factors that improve the functioning of HRTs, leading them to respond to disastrous events and work together effectively under intense time pressure and dynamic conditions.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…If the project's timescale cannot be changed, one logical recommendation emerging from this analysis would be to begin such collaborative projects with an explicit description of science teachers’ expertize, which would enable scientists to view teachers as experts and would provide all participants with a foundational perspective on the richness of science teachers’ expertize. Grutterink et al (), for example, examined the impact of expertize affirmations like this in business teams at the beginning of short‐term collaborative work. They found that these affirmations are valuable, but only in teams with a strong pre‐existing mutual recognition as experts.…”
Section: Discussionmentioning
confidence: 99%
“…To give another example, if team members are well informed about each other's expertise, because all team members clearly voice their capabilities, this will positively affect team performance; because tasks can be assigned to the right person, capabilities will be used properly and coordination of team activities will be facilitated (e.g. Grutterink, Van der Vegt, Molleman, & Jehn, 2013). However, if the manipulations of perceptions result in unrealistic and overstated perceptions of the qualifications of the focus person, this is likely to lead to poor managerial decisions.…”
Section: Theory and Hypothesesmentioning
confidence: 99%